Poligami Perspektif Teori Double Movement Fazlur Rahman - N. Nafisatur Rofiah (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2020)
Writing this scientific article aims to describe polygamy from the perspective of the double movement theory of Fazlur Rahman. Through understanding, this theory can provide an explanation to understand and explore verses 3 of the suras about polygamy which by the jurists are considered as the legitimate principle of marriage according to Islam. The methodology used in writing scientific articles is the research methodology using the literature review. The literature review is one type of qualitative research that contains a description of theories, findings, and other research materials. The primary data source is Fazlur Rahman's works related to the theory of double movement, while other works are used as secondary data. The method of data collection is documentation and using content analysis as an analysis. The research findings show that the importance of understanding the verses of the Qur'an from various scientific perspectives is needed. Double movement is a theory carried out by an interpreter of the Qur'an. Using this theory of double movement that polygamy is not permissible in our present context.Keywords: Polygamy, Double Movement, Fazlur Rahman.